Evolutionary Relationship of Disease Resistance Genes in Soybean and Arabidopsis Specific for the Pseudomonas syringae Effectors AvrB and AvrRpm1. Issue 1 (17th July 2014) - Ashfield, Tom; Redditt, Thomas; Russell, Andrew; Kessens, Ryan; Rodibaugh, Natalie; Galloway, Lauren; Kang, Qing; Podicheti, Ram; Innes, Roger W.
Abstract : Polymorphisms in the leucine-rich-repeat domains of two closely related soybean genes allow them to distinguish between two pathogen effectors detected by a single disease resistance gene in Arabidopsis. Abstract: In Arabidopsis ( Arabidopsis thaliana ), the Pseudomonas syringae effector proteins AvrB and AvrRpm1 are both detected by the RESISTANCE TO PSEUDOMONAS MACULICOLA1 ( RPM1 ) disease resistance (R) protein. By contrast, soybean ( Glycine max ) can distinguish between these effectors, with AvrB and AvrRpm1 being detected by the Resistance to Pseudomonas glycinea 1b (Rpg1b) and Rpg1r R proteins, respectively. We have been using these genes to investigate the evolution of R gene specificity and have previously identified RPM1 and Rpg1b . Here, we report the cloning of Rpg1r, which, like RPM1 and Rpg1b, encodes a coiled-coil (CC )-nucleotide-binding (NB )-leucine-rich repeat (LRR ) protein. As previously found for Rpg1b, we determined that Rpg1r is not orthologous with RPM1, indicating that the ability to detect both AvrB and AvrRpm1 evolved independently in soybean and Arabidopsis. The tightly linked soybean Rpg1b and Rpg1r genes share a close evolutionary relationship, with Rpg1b containing a recombination event that combined a NB domain closely related to Rpg1r with CC and LRR domains from a more distantly related CC -NB -LRR gene. Using structural modeling, we mapped polymorphisms between Rpg1b and Rpg1r onto the predicted tertiary structure of Rpg1b, which revealed highly polymorphic surfaces within both the CC and LRR domains. Assessment of chimeras between Rpg1b and Rpg1r using a transient expression system revealed that AvrB versus AvrRpm1 specificity is determined by the C-terminal portion of the LRR domain. The P. syringae effector AvrRpt2, which targets RPM1 INTERACTOR4 (RIN4) proteins in both Arabidopsis and soybean, partially blocked recognition of both AvrB and AvrRpm1 in soybean, suggesting that both Rpg1b and Rpg1r may detect these effectors via modification of a RIN4 homolog.